The Spatial Distribution of Human Capital: Can It Really Be Explained by Regional Differences in Market Access? - Enrique López-Bazo; Burhan Can Karahasan (European Regional Science Association (ERSA), 2011)
This paper checks for the robustness of the estimate of the impact of market access on the regional variability of human capital, derived from the NEG literature. The hypothesis is that the estimate of the coefficient of the measure of market access is actually capturing the effect of regional differences in the industrial mix, and the spatial dependence in the distribution of human capital. Results for the Spanish provinces indicate that the estimated impact of market access vanishes and becomes non-significant once these two elements are included in the empirical analysis.
Keywords: 330